Penerimaan Audiens Pada Konten Campaign untuk Palestina di Akun Instagram @ariekuntung - Lina Yuniati; Tutiasri, Ririn Puspita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study discusses the audience's acceptance of the campaign content for Palestine on the Instagram account @ariekuntung. The content is in the form of embedded content on Arie Untung's Instagram account, the content shows several female public figures reading poetry as a form of support for Palestine and the second content contains Arie Untung's invitation to the public, especially his followers, to take action to take to the streets. The Instagram account @ariekuntung is known to be active in voicing support for Palestine where Arie Untung uses this platform for social campaigns, sharing the latest information, inviting participation in mass actions, donating, and encouraging solidarity with Palestine. The success of this campaign message depends not only on its content, but also on how the audience receives and responds to it. Audience acceptance is influenced by various factors such as social background, culture, education, and how the message is delivered. In the campaign for Palestine, audience acceptance becomes more complex because the Palestinian issue involves sensitive political, humanitarian, and religious aspects. Through various uploads that are informative, persuasive, and emotional, @ariekuntung's posts have attracted the attention of many followers who show varying responses to the content posted. The content shared by Arie Untung has raised various opinions from the audience regarding the posts shared, this is because it is seen from the credibility and background of his public figure. This study aims to analyze how the audience receives, understands, and responds to the campaign content. This study uses a qualitative approach with a descriptive method, and applies reception analysis developed by Stuart Hall. Data collection was carried out through in-depth interviews and documentation. The number of informants in this study was 8 people. From the results of the interviews and analysis that have been carried out by the researcher, it was found that 5 people were included in the dominant hegemonic position category, namely informants 1, 2, 5, 7, and 8. Then 3 other people were included in the negotiated position category, namely informants 3, 4, and 6. The researcher did not find any informants in the oppositional position. Keywords: Audience Reception, Palestine Campaign, Instagram Content